2018
DOI: 10.1017/s2045796018000549
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of global functioning and quality of life in people with psychotic disorders

Abstract: AimsPeople with psychotic disorders face impairments in their global functioning and their quality of life (QoL). The relationship between the two outcomes has not been systematically investigated. Through a systematic review, we aim to explore the presence and extent of associations between global functioning and QoL and establish whether associations depend on the instruments employed.MethodsIn May 2016, ten electronic databases were searched using a two-phase process to identify articles in which associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 78 publications
(145 reference statements)
5
44
0
2
Order By: Relevance
“…A recent review emphasised that there is an association between low social functioning and negative QoL in psychotic disorders [ 103 ]. The results indicated that factors such as social integration, mobility and adjustment may be more relevant for QoL than mere illness factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review emphasised that there is an association between low social functioning and negative QoL in psychotic disorders [ 103 ]. The results indicated that factors such as social integration, mobility and adjustment may be more relevant for QoL than mere illness factors.…”
Section: Discussionmentioning
confidence: 99%
“…This dissociation is not surprising because a recent meta-analysis suggests that functioning has weaker correlations with subjective QoL than with objective QoL (i.e. evaluated by an interviewer) 40 and because the two facets of QoL do not share the same predictors. 7 Overall, these findings reaffirm the interest and specificity of subjective measures that are not accessible to hetero-evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Social functioning (as continuous outcome), as measured by overall change scores on any validated global assessment of functioning scales such as Global Assessment of Functioning (GAF) scale or quality of life scales. [ 35 ]…”
Section: Methods and Analysismentioning
confidence: 99%